A highly selective "ON–OFF" probe for colorimetric and fluorometric sensing of Cu2+ in water. Issue 19 (13th February 2017) - Naskar, Barnali; Modak, Ritwik; Maiti, Dilip K.; Bauzá, Antonio; Frontera, Antonio; Maiti, Pulak Kumar; Mandal, Sukhendu; Goswami, Sanchita
Abstract : A new diformyl phenol based probe for selective detection of Cu 2+ in aqueous medium, applicable for cell imaging in Vero cells. Theoretical studies were performed to establish the underlying keto–enol tautomerism and optimization of the Cu 2+ complex. Abstract : We present herein a diformyl phenol based probe, 3-(3-[2, 3-dihydroxy-propylimino-methyl]-2-hydroxy-5-methyl-benzylidene-amino)-propane-1, 2-diol (H5 dpm ), as a colorimetric and fluorometric chemosensor for selective detection of Cu 2+ in aqueous solution under physiological conditions. This simple system produces a colorimetric change enabling naked eye detection as well as on–off fluorescence response towards Cu 2+ in an aqueous medium with a detection limit of 11.2 nM. To further demonstrate the utility ofH5 dpm, we next explored the application ofH5 dpm for imaging Cu 2+ in Vero cells. The attractive imaging properties of theH5 dpm probe will open up avenues for molecular imaging and biomedical applications.